Reconstructing the History of Doing Theology at UWC : Some Fragmentary Decolonial Perspectives - Conradie, Ernst M. (Stellenbosch Theological Journal, 2022)
The history of the University of the Western Cape is a history born amidst colonisation but also one of decolonisation and the emergence of decolonial thinking. This contribution sketches these movements from a point of departure in a private letter from the then Prime Minister HF Verwoerd to Prof Kalie Heese (Psychology) on the future of the then University College of the Western Cape (dated 2 October 1962). This will, in rather graphic terms, illustrate the challenges posed by tertiary education under conditions of colonial rule. Against that background, subsequent sections explore the history of UWC and of doing theology at UWC from one possible, fragmentary decolonial perspective. Several qualifications are offered on how to approach and not to approach doing systematic theology at UWC before eight soteriological themes that have been prominent in theological discourse at UWC are outlined, namely conversion / transformation, unity / ecumenicity, reconciliation, justice, human dignity, liberation, reconstruction / development and the integrity of creation. Finally, it is suggested that the remarkable reception of Gustaf Aulén's Christus Victor typology at UWC is indicative of the always uneasy counter-intuitive attempt to hold together liberation, evangelical / reformed and liberal theologies - that is perhaps epitomised by UWC.